Help-seeking Behaviours among Youth Drug Abusers in Kuching, Sarawak - Sim, Joan Jo Jo (Universiti Malaysia Sarawak (UNIMAS), 2021)
The trend of drug abuse is increasing in Malaysia and a significant number of them are youths. Past studies discovered that youths do not seek professional help or do not even seek help when they are abusing drugs. Thus, it is important to understand the experience of the young drug abusers and their journey before they got admitted into the rehabilitation centre. This is crucial as drug abusers are always hiding their identity. Therefore, the study aims to explore the experience of drug abusing youths in their journey of help-seeking. Methodologically, the study employs qualitative approach to have in-depth understanding about the help-seeking behaviour and pattern of the young drug addicts in the rehabilitation centre. The study is carried out in the Cure & Care Clinic in Kuching area targeting the youths who are currently undergoing treatment in the centre. The sampling is identified using purposive technique. Instruments used for the study includes in-depth interview by using guided interview questions. The findings are analysed using content analysis to develop themes through the verbatim data. The study enquires about their experiences on drug abuse and their journey to the rehabilitation centre. Thus, the major finding indicates their experience before and after their admission to the centre. There are many factors which contribute to their drug abuse but majority of them were influenced by their peers. Most of the respondents never had the intention to seek help until the family members took action. The admission helps some of the youth to start having the intention in seeking help, improving the relationship with family members and having some positive changes on themselves. The findings of the study have implications on the community with the drug abusing youth in prevention and recovery policy. Keywords: Drug abuse, youth, help-seeking, admission, rehabilitation centre